2010
DOI: 10.1089/ten.tec.2009.0800
|View full text |Cite
|
Sign up to set email alerts
|

Tissue Engineering by Molecular Disassembly and Reassembly: Biomimetic Retention of Mechanically Functional Aggrecan in Hydrogel

Abstract: In vitro assembly of key functional extracellular matrix constituents for tissue-engineered constructs may provide a tool to modulate the retention of proteoglycan (PG) aggregates, which are crucial to compressive biomechanical properties of connective tissues. This study tested the hypotheses that (1) biomimetic molecular reassembly of PG aggregates (native aggrecan [AGC] with hyaluronan [HA] AE link protein [LP]) affects AGC retention kinetics in hydrogel constructs, (2) the compressive properties of such hy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 52 publications
0
8
0
1
Order By: Relevance
“…Initial thickness can be controlled well due to low p PG with low GAG concentration, 4 which could be balanced by the restraining force of agarose, consistent with our previous study. 13 The swelling of the PG-containing constructs (Groups II and IV) beyond the thickness of agarose only or COL-containing constructs (Groups I and III) after compaction indicates the presence of swelling pressure exerted by PG that was restrained with the increased thickness in the agarose gel network. A mechanism for providing higher restraining force with a smaller increase in construct thickness after compaction may be useful in further retention of the compacted state of the constructs and to further increase the matrix concentrations.…”
Section: Han Et Almentioning
confidence: 93%
See 2 more Smart Citations
“…Initial thickness can be controlled well due to low p PG with low GAG concentration, 4 which could be balanced by the restraining force of agarose, consistent with our previous study. 13 The swelling of the PG-containing constructs (Groups II and IV) beyond the thickness of agarose only or COL-containing constructs (Groups I and III) after compaction indicates the presence of swelling pressure exerted by PG that was restrained with the increased thickness in the agarose gel network. A mechanism for providing higher restraining force with a smaller increase in construct thickness after compaction may be useful in further retention of the compacted state of the constructs and to further increase the matrix concentrations.…”
Section: Han Et Almentioning
confidence: 93%
“…For the mechanical compaction of the constructs, the constructs were placed in a radially confining chamber between two porous platens filled with PBS + PIs and compressed to a final compression of 90% of the initial thickness using a mechanical spectrometer. 13 The constructs were compressed to 30%, 60%, 75%, and 90% of the initial thickness during a 1600-s ramp compression, followed by 2400-s relaxation to equilibrium. At each compression level, s PEAK and s EQ were calculated from the measured load at the end of ramp compression and at the end of relaxation, divided by the area of the disk.…”
Section: Mechanical Compaction Of the Constructsmentioning
confidence: 99%
See 1 more Smart Citation
“…Once we overcome this challenge, we may focus on assessing the ultrastructural organization of the deposited collagen matrix relative to the native tissue, as other researchers have approached using a variety of techniques such as electrospinning, in vitro proteoglycan assembly, magnetic fibril alignment, and 3D bioprinting. 12,[74][75][76][77] With regard to (b), we have recently observed that young adult human chondrocytes, isolated from expired osteochondral allografts from a tissue bank, exhibit chondrogenic potential nearly comparable to that of immature bovine chondrocytes. 49 Therefore, we plan to further investigate this source of human cells in our effort to translate our tissue engineering approach to the clinic.…”
Section: Fig 9 Study 2 Construct Functional Properties: (A) E Y (B)mentioning
confidence: 99%
“…3,4 The field of CTE has seen numerous advancements and produced a broad array of in vitro techniques for the cultivation of neocartilage, yet the vast majority of studies focus on small (3-6 mm diameter) tissue constructs. [5][6][7][8][9][10][11][12] Chondrocyteagarose constructs have proven to be an efficient model system, particularly when cultured in ITS media with transforming growth factor (TGF)-b supplementation. 6,[13][14][15][16][17][18] Using this system, our group consistently reproduces native cartilage equilibrium compressive Young's modulus (E Y ) and glycosaminoglycan (GAG) content in Ø4 mm constructs using either primary or passaged bovine chondrocytes.…”
mentioning
confidence: 99%